Исповедь книгочея, который учил букве, а укреплял дух - Рабинович Вадим Львович (Книга, 1991)
Экземпляры: аб. (1991) / Инвентарный номер: 33429 / Цена: / Сис.шифр: 86.212 / Авт.знак: Р12 / ГРНТИ: 17 / ББК: 86.212